SOME ASPECTS OF VIOLENCE IN SPORT - Bećir Šabotić (Sport Mont, 2010)
Today we are very often faced with the appearance of the violence in sport field and fighting places and for that reason there are some demands that it can be studied from a social aspect. This is not only a problem of a personal nature but also a problem of a wider social community. There are some firm attitudes that sport serves the man in many cases and it has a goal to increase the social aspect that means coming close to the people. However, attitudes like that have remained only in paper. The day that the professionalism has taken the domination in sport, everything went around in the opposite direction because the result is important in realization of planned professionalism. Going to that goal, trainers who are often autocratic, compel the sportsman on doing the task no matter what, taking him the possibility to freely express his individuality. The sport bureaucracy is being formed around the player, sportsman, who is than capable to manage even the managerial stuff. The even chase between the sport commercialization and professionalism has brought to that that it becomes very profitable job in which you can earn a lot. That is why we are more and more distanced from the real value of the sport. In return, we got sport competitions which are more presented with violence and brutality. The rules of behavior are being neglected which causes more violent behavior. Cruel behavior towards the athletes is more intensive and so it is one of the most shown sights of violence in sport which are shown through the training duration. We are often the witnesses that all the efforts overlook even the physiological bounds. Doping consumation has shown the brutal violence towards the athletes which hasn’t missed our country. One of the symptoms of violence in sport is connected with the trainings and competitions of the little children. Sport stadiums have, unfortunately, become the place of those people who, using the conditions and ambient, often go with local, national and even chauvinistic slogans. In democratic society physical education must be free and human. Doing that we would come to the more human relationships in sport, relationships in which the man wouldn’t be burdened of the victory imperative in any case, to sport without the violence and brutality.